FUNDAMENTAL ISSUES OF ORTHODOX ECCLESIOLOGY AT SAINT JOHN CHRYSOSTOM / ASPECTE FUNDAMENTALE ALE ECLESIOLOGIEI ORTODOXE LA SFÂNTUL IOAN GURĂ DE AUR - BUT-CĂPUȘAN, Dacian (Studia Universitatis Babeș-Bolyai Theologia Orthodoxa, 2015)
St. John Chrysostom addresses all the aspects of Orthodox ecclesiology. The Church, the Body of Christ, is a sacramental communion of the faithful with Christ and with each other. The communion between the human and the divine is achieved in the Church through the Holy Eucharist. The Church is divine guide, its role is sanctifying; outside of it man cannot attain salvation. Ordination is not a simple ceremony, but it has a sacramental character. Through the laying on of the hands of the Bishop candidates receive the grace of the priesthood. Hierarchy is a permanent reality of sacramental nature. In Chrysostom’s views, the terms institution and event – much debated in current ecclesiology – represent two aspects of a single divine action in history. Sfântul Ioan Gură de Aur tratează toate aspectele eclesiologiei ortodoxe. Biserica, Trupul lui Hristos este o comuniune sacramentală, a credincioșilor cu Hristos și întreolaltă. Comuniunea dintre uman și divin se realizează în Biserică, prin Sfânta Euharistie. Biserica este îndreptar divin, rolul ei este sfințitor, în afara ei omul nu poate realiza mântuirea. Hirotonia nu este o simplă ceremonie, ci are caracter de Taină. Prin punerea mâinilor arhiereului candidații primesc harul preoției. Ierarhia este o realitate permanentă, de natură sacramentală. Iar termenul de instituție și cel de eveniment, despre care se vorbește atât de mult în eclesiologia actuală, reprezintă în concepția hrisotomică două aspecte ale unei singure acțiuni divine în istorie.